Nursing Leadership Models in Promoting and Improving Patient's Safety Culture in Healthcare Facilities; A Systematic Review - Yodang Yodang; Nuridah Nuridah (Shahid Sadoughi University of Medical Sciences, 2020)
Background: Nurse leader has an important role in encouraging patient's safety culture among nurses in the healthcare system. This literature review aims to identify the nursing leadership model and to promote and improve patient safety culture to improve patient outcomes in health care facilities including hospitals, primary health care, and nursing home settings. Methods: Searching appropriate journals through some journal databases were applied including DOAJ, GARUDA, Google Scholar, MDPI, Proquest, Pubmed, Sage Journals, ScienceDirect, and Wiley Online Library, which were published from 2015 to 2020. Results: Fourteen articles meet the criteria and are included in this review. The majority of these articles were retrieved from western countries, the US, Canada, and Finland. This review identifies three nursing leadership models that seem useful to promote and improve patient safety culture in health care facilities which are transformational, authentic, and ethical leadership models. Conclusion: The patient safety influences health care outcomes. The evidence shows the leadership has positive relation to patient satisfaction and patient safety outcomes improvement. The transformational, authentic, and ethical leadership models seem to be more useful in promoting, maintaining, and improving patient safety culture in health care facilities.